1991
DOI: 10.3758/bf03207541
|View full text |Cite
|
Sign up to set email alerts
|

Duration discrimination of filled and empty auditory intervals: Cognitive and perceptual factors

Abstract: Adult subjects were presented with two auditory stimuli per trial, and their task was to decide which ofthe two was longer in duration. An adaptive psychophysical procedure was used. In Experiments 1, 2, and 4, the base duration was 50 msec, whereas in Experiment 3, the base duration was 1 sec. In Experiments 1,2, and 4, it was found that filled intervals (continuous tones) were discriminated more accurately than empty intervals (with onset and offset marked by clicks). It was concluded that this difference wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

21
213
5
5

Year Published

1992
1992
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(244 citation statements)
references
References 33 publications
21
213
5
5
Order By: Relevance
“…Time measurement has also been shown to have quite different properties at these two duration ranges. For instance, psychophysical characteristics differ (Gibbon, Malapani, Dale, & Gallistel, 1997), pharmacological agents (Mitriani, Shekerdijiiski, Gourevitch, & Yanev, 1977;Rammsayer, 1999) and the distraction of attention in dual task scenarios (Rammsayer & Lima, 1991) can have differential influence (but see Macar, Grondin, & Casini, 1994), while lesions to specific brain areas elicit differential impairments (Clarke, Ivry, Grinband, Roberts, & Shimizu, 1996). Based on these observations, several authors (Gibbon et al, 1997;Hazeltine, 1997;Ivry, 1996;Lewis & Miall, 2003;Rammsayer, 1999) have hypothesised that time intervals in the millisecond and multisecond ranges are measured by independent brain mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Time measurement has also been shown to have quite different properties at these two duration ranges. For instance, psychophysical characteristics differ (Gibbon, Malapani, Dale, & Gallistel, 1997), pharmacological agents (Mitriani, Shekerdijiiski, Gourevitch, & Yanev, 1977;Rammsayer, 1999) and the distraction of attention in dual task scenarios (Rammsayer & Lima, 1991) can have differential influence (but see Macar, Grondin, & Casini, 1994), while lesions to specific brain areas elicit differential impairments (Clarke, Ivry, Grinband, Roberts, & Shimizu, 1996). Based on these observations, several authors (Gibbon et al, 1997;Hazeltine, 1997;Ivry, 1996;Lewis & Miall, 2003;Rammsayer, 1999) have hypothesised that time intervals in the millisecond and multisecond ranges are measured by independent brain mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are many results from psychophysical (Rammsayer & Lima, 1991 ;Karmarkar & Buonomano, 2007) and pharmacopsychological studies (Rammsayer, 1992a(Rammsayer, , 1993(Rammsayer, , 1997(Rammsayer, , 1999(Rammsayer, , 2006 that cannot be explained by a single timing mechanism for the whole range of time. These findings support the idea of two (or even more) different timing mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Whether the interval to be timed is filled or empty also affects temporal perception in both humans (Abel, 1972a(Abel, , 1972bGrondin, 1993;Rammsayer & Lima, 1991) and pigeons (Mantanus, 1981). Although Mantanus (1981) reported that pigeons' temporal discriminations were more accurate with filled intervals than with empty intervals, the interpretation of this effect is ambiguous because of a number of design and general test procedure problems, which were described by Kraemer, Randall, and Brown (1997).…”
mentioning
confidence: 99%